540:{90+96:[6-(125÷25+1)]×4}=
Răspunsuri la întrebare
Răspuns de
1
540:{90+96:[6-(5+1)]x4}=
540:[90+96:[6-4]x4]=
540:90+96:2x4=
540:90+48x4=
6+192=
198
Sper că te-am ajutat ! ★♡✩♡★♡✩♡★
540:[90+96:[6-4]x4]=
540:90+96:2x4=
540:90+48x4=
6+192=
198
Sper că te-am ajutat ! ★♡✩♡★♡✩♡★
Alte întrebări interesante
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă